R. Alan Culpepper – Jörg Frey (eds.), The Opening of John’s Narrative (John 1:19–2:22). Historical, Literary, and Theological Readings from the Colloquium Ioanneum 2015 in Ephesus (WUNT 385; Tübingen: Mohr Siebeck 2017) - Darowski, Łukasz Tomasz (The Biblical Annals, 2021)
Book Review: R. Alan Culpepper – Jörg Frey (eds.), The Opening of John’s Narrative (John 1:19 – 2:22). Historical, Literary, and Theological Readings from the Colloquium Ioanneum 2015 in Ephesus (WUNT 385; Tübingen: Mohr Siebeck 2017)